The Effect of Six-week Low Intensity Plyometrics Training on Leg Muscles Power of Young Pencak Silat Athletes - Inosen Lingsir Maghribi; Elsa Aulia Putri (JUMORA: Jurnal Moderasi Olahraga, 2026)
Pencak silat is a martial sport that requires high explosive power of the leg muscles to support kick effectiveness, position change, and quick movement response during matches. The purpose of this study was to determine the effect of low-intensity plyometric training for six weeks on the power ability of leg muscles in young pencak silat athletes. The sample in this study was 20 male pencak silat athletes at Garuda Silat Academy with an average age of 15.35 years (SD = +- 0.58). This study uses a quasi-experimental method with a one group pretest–posttest design. Leg muscle power is measured using a standing broad jump. The difference test used a paired samples t-test with a significance level of 0.05 and the data was analyzed using SPSS version 27.0.1.0. The results showed a Sig. (2-tailed) value of <.001 which means there was a significant improvement after the intervention, leg muscle power measured using the standing broad jump increased by an average of 13.2-centimeters. In conclusion, six weeks of low-intensity plyometric training using a jumps-in-place model effectively enhanced lower-limb explosive power in adolescent pencak silat athletes. It is recommended that coaches consider incorporating progressively designed low-intensity plyometric exercises into long-term training programs, as they are safe, practical, and appropriate for supporting neuromuscular development while minimizing injury risk in young athletes.